Analisis Kondisi dan Pengembangan Infrastruktur Pariwisata di Pantai OTA Kabupaten Gorontalo: Pendekatan Kolaboratif Pemerintah, Masyarakat, dan Swasta - Utina, Majid; Eraku, Sunarty; Yusuf, Daud (Universitas Negeri Gorontalo, 2025)
Tourism is an important sector that contributes significantly to the regional economy, including in Gorontalo Regency. This study aims to map the condition of infrastructure and management at three main beaches, namely Obos Beach, Tilalohe Beach, and Aryan by Kadena Beach, as well as to analyze their impact on tourist attraction and the welfare of the local community. The research method uses a descriptive approach with data collection through observation, interviews, and documentation. The results show that the three beaches already have adequate basic facilities such as toilets, dining areas, and parking lots, but access roads to the locations remain the main obstacle that needs improvement to enhance tourist comfort. Cleanliness and security management at Aryan by Kadena Beach is more intensive compared to the other beaches, contributing to increased visitor comfort. The role of the village government and local communities is very important in the development of sustainable tourism, although there are budget limitations in some locations. Environmental preservation programs such as tree planting are also carried out to maintain the beach ecosystem while serving as an additional attraction for tourists. Promotion through social media and capacity building of tourism management human resources are supporting factors in increasing tourist visits. In conclusion, infrastructure improvement, strengthening the role of the village government, community empowerment, and sustainable management of cleanliness and security are the main keys to optimizing the tourism potential in Gorontalo Regency